1997
DOI: 10.1111/j.1699-0463.1997.tb00593.x
|View full text |Cite
|
Sign up to set email alerts
|

The clonal antibody response to Pseudomonas aeruginosa heat shock protein is highly diverse in cystic fibrosis patients

Abstract: M., Hanson, L. 8. & Heriby, N. The clonal antibody response to Pseudomonas aeruginosa heat shock protein is highly diverse in cystic fibrosis patients. APMIS 105: 449456, 1997.The GroEL protein of Pseudoomonas aeruginosa belongs to the bacterial 60-65 kDa heat shock protein family. A strong antibody response to GroEL has been found in cystic fibrosis (CF) patients with chronic pulmonary infection caused by P. aeruginosu. Clonotypes of IgGl and IgG2 antibodies against GroEL were studied in 60 consecutive sera f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…GroES, HtpG, and GroEL were significantly downregulated. Previous work has shown that CF patients produce antibodies to GroEL (Ulanova et al, 1997 ). Other recent work has shown that heat shock proteins such as GroES and HtpG are actually downregulated in biofilms (Patrauchan et al, 2007 ).…”
Section: Resultsmentioning
confidence: 98%
“…GroES, HtpG, and GroEL were significantly downregulated. Previous work has shown that CF patients produce antibodies to GroEL (Ulanova et al, 1997 ). Other recent work has shown that heat shock proteins such as GroES and HtpG are actually downregulated in biofilms (Patrauchan et al, 2007 ).…”
Section: Resultsmentioning
confidence: 98%
“…This suggests PIA‐AMV may cause protein misfolding, which would cause upregulation of chaperones to maintain the cellular integrity. Previously, it has been observed that chronically infected CF patients have a high antibody titre against GroEL (Ulanova et al ., 1997). Since PIA‐AMV seems to upregulate GroEL (Table 2), this further suggests PIA‐AMV mimics the CF lung condition.…”
Section: Resultsmentioning
confidence: 99%
“…GroEL is among the most highly conserved proteins in nature (Segal & Ron, 1996), and functions together with GroES to maintain protein integrity, which enables cells to survive a variety of environmental stresses (Hendrick & Hartl, 1993). A strong antibody response to GroEL has been found in cystic fibrosis patients with chronic pulmonary infection caused by P. aeruginosa (Ulanova et al, 1997), which suggests a role for PhrS under these conditions. The outer membrane porin OprD has been shown to facilitate diffusion of basic amino acids as well as of small peptides, and also serves as a channel for the b-lactam antibiotic imipenem (Trias & Nikaido 1990), whereby the loss of OprD can lead to imipenem resistance (Lynch et al, 1987).…”
Section: Proteome Analyses Upon Overproduction Of Phrsmentioning
confidence: 99%